KAJIAN EPIDEMIOLOGI PENYAKIT INFEKSI SALURAN PENCERNAAN YANG DISEBABKAN OLEH AMUBA DI INDONESIA - -, Anorital; Andayasari, Lelly (Media Penelitian dan Pengembangan Kesehatan, 2011)
The intestinal infection caused by amoeba is one of the three diarrhea causes appears to be a public health problem with high incidence in the community. Amebiasis is caused by Entamoeba histolytica, can be differentiated from non pathogen Entamoeba hartmanni and Entamoeba coli. Morphologically of Entamoeba histolytica and Entamoeba dispar are very similar. However, based on the diagnosis utilizing molecular examination technique, in fact, the main cause of amebiasis is Entamoeba dispar. Amoeba dysentry can be found arround the world, having cosmopolite characteristic with incidences varying between 3-10%. In the developed countries with relatively better hygiene and sanitation, amoebiasis incidence is between 2-11%. In Indonesia, the amoebiasis incidence is`quite high, in the range of 10-18%. Whereas the mortality caused by amoebiasis is high enough between 1.9?9.1%, second rank after malaria. Several kinds of amoeba dysentri medicines were used, but Metronidazole is proven as the effective drug of choice for Entamoeba histolytica, both the cyste and trophozoite forms with minor side effect to the patients. Good personal hygiene and environmental sanitation practices are the major factors of this disease prevention. The main principle to prevent the spreading of amoebiasis infection is to cut the link of infection sources to human beings. Personal hygiene is focused on the management of individual behaviour, meanwhile environmental sanitation prevention focus lies on the better environmental management to cut the link of disease cycle.